2009
DOI: 10.3390/rs1030375
|View full text |Cite
|
Sign up to set email alerts
|

Operational Ship Monitoring System Based on Synthetic Aperture Radar Processing

Abstract: This paper presents a Ship Monitoring System (SIMONS) working with Synthetic Aperture Radar (SAR) images. It is able to infer ship detection and classification information, and merge the results with other input channels, such as polls from the Automatic Identification System (AIS). Two main stages can be identified, namely: SAR processing and data dissemination. The former has three independent modules, which are related to Coastline Detection (CD), Ship Detection (SD) and Ship Classification (SC). The later … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 5 publications
(6 reference statements)
0
27
0
Order By: Relevance
“…Such techniques mainly involve applications related to ship detection, land mask estimation in those situations where geographic maps cannot be used (natural disasters, marshlands and wetlands) and oil-spill detection, among others. Furthermore, maritime applications have become one of the SAR major fields of study in recent years [19][20][21][22][23][24]. All in all, the absence of studies of this particular issue along with the difference it can make in automatic processing, make this topic an interesting one to cover.…”
Section: Introductionmentioning
confidence: 99%
“…Such techniques mainly involve applications related to ship detection, land mask estimation in those situations where geographic maps cannot be used (natural disasters, marshlands and wetlands) and oil-spill detection, among others. Furthermore, maritime applications have become one of the SAR major fields of study in recent years [19][20][21][22][23][24]. All in all, the absence of studies of this particular issue along with the difference it can make in automatic processing, make this topic an interesting one to cover.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the detection of small vessel may be improved by using corner reflectors, as proposed in (Stastny et al, 2014). An operational ship monitoring system based on SAR processing is presented in (Margarit et al, 2009). …”
Section: Sar For Vessel Surveillancementioning
confidence: 99%
“…Margarit et al presented a vessel classification algorithm based on fuzzy logic. Experimental results based on the ENVISAT-ASAR and ERS data at a resolution of approximately 30 meters showed that the preliminary percentage of positive classifications was approximately 70% [3,13]. In medium resolution SAR images (30 to 10 m), energy scattered from different parts of a vessel usually overlap in a few pixels.…”
Section: Introductionmentioning
confidence: 99%